Changes in plasma tryptophan/branched chain amino acid ratio in responses to training volume variation - Tanaka, H.; West, K. A.; Duncan, G. E.; Bassett, D. R. (International Journal of Sports Medicine, 1997)
The major symptoms of overtraining including decreased exercise performance, altered mood states, and depleted muscle glycogen stores closely resemble the effects of brain serotonin, the level of which is dependent on the plasma ratio of tryptophan to branched-chain amino acids (BCAA). To examine the relation between plasma amino acids and overtraining, ten highly-trained endurance runners underwent two weeks of base training (normal training) before increasing their training volume by 40% for two weeks to achieve a state of short-term overtraining (or overreaching). The overtraining period was followed by two weeks of recovery in which training volume was reduced by 41% of the base training. For the whole group, no significant changes were observed in running economy and maximum oxygen uptake. There were no changes in resting heart rate, blood pressure, resting metabolic rate, and serum cortisol level in response to the changes in training volume. The runners experienced a significant increase (p < 0.05) in fatigue score for the profile of mood states when the training volume was increased. The elevated fatigue score returned to baseline when the training volume was reduced. Plasma free or total tryptophan, BCAA, and the tryptophan/BCAA ratio were not significantly altered throughout the course of this study. We concluded that proposed physiological markers of overtraining, including plasma tryptophan and BCAA levels, were unchanged despite a 40% increase in training volume.